PENERAPAN TEKNOLOGI LITERASI DALAM MEMBENTUK KREATIVITAS ANAK PONDOK TAHFIDZ NURUUL MILLAH - Nurani, Siti Shafaa’; Riyanti, Nita; Herdianti, Nurul Azmi; Saputri, Cindy; Akmalia, Alifa Shafa; Laksono, Pandu Jaya; Hamdan, Ahmad; Laksono, Bayu Adi (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Educational technology literacy is a system that is used to support learning. In the service carried out, the educational technology used in its implementation is administrative tools and learning media. Children's development is influenced by their creativity capacity, which allows them to express their thoughts and discover new things so that they can think creatively, provide a good stimulus for children and can increase their creativity. Their development is influenced by all aspects in their environment such as family, playmates and even technology and information that develops in their time. This service is carried out for character direction in children regarding educational technology that can be used in learning, as well as the introduction of positive impacts and negative impacts of technology. The method of implementation is carried out by determining the location of the activity, determining the procedure of the activity, determining the time of implementation, implementing the activity and evaluating the activity to find the results of the service, namely children can practice how to do learning by using learning media, and can mention what are the negative and positive impacts of educational technology, and can know what to do if there is social deviation caused by technology